We want to establish a string of equalities.
That string will use several substitutions which involve basis expansions,
so it is helpful to state those basis expansions first.
Since (vj)1≤j≤n is a basis for V, there exists (xj)1≤j≤n such that
vexpanding v∈V=in terms of the (vj)1≤j≤n basis of Vv1x1+⋯+vnxn.
Since (wi)1≤i≤m is a basis for W, there exists (aij)1≤i≤m,1≤j≤n such that
v1Lexpanding v1L∈W=in terms of the (wi)1≤i≤m basis of W{w1a11⋮wmam1},…,vnLexpanding vnL∈W =in terms of the (wi)1≤i≤m basis of W{w1a1n⋮wmamn}
(Note:
The column vectors of (aij)1≤i≤m,1≤j≤n, written horizontally,
combine to form the transpose of Mvw(L).)
So,
{w1(vL)1⋮wm(vL)m}expanding vL∈W=in terms of the (wi)1≤i≤m basis of WvLexpanding v∈V=in terms of the (vj)1≤j≤n basis of V(v1x1+⋯+vnxn)LL=linearv1Lx1+⋯+vnLxn=expanding each vjL∈W=in terms of the (wi)1≤i≤m basis of W(v1L={w1a11⋮wmam1})x1+⋯+(vnL={w1a1n⋮wmamn})xndist., Fubini,=dist.{w1(A1⋅X)⋮wm(Am⋅X)}
w1(A1⋅X)=w1(∑nj=1a1jxj)w1a11x1…w1a1nxn⋮⋮⋮⋮wm(Am⋅X)=wm(∑nj=1amjxj)wmam1x1…wmamnxnm∑i=1n∑j=1wiaijxj‖
---------------
To some extent this follows the notation and setup of Chapter IV, Section 3 of Serge Lang's Linear Algebra, 3e.
The notation deviates from that in these ways:
1. If f is a function and v is in the domain of f, we write the value of f at v any of three ways: f(v) or fv or vf.
As long as it is known which is a function and which can be an argument to that function, that should not be a problem.
2. Sometimes we have a column of values which need to be added up.
We introduce a notation which gives a vertical version of the standard symbol \Sigma for summation.
For example,
\begin{Bmatrix} {} v_1 \\ \vdots \\ v_n \end{Bmatrix} = \sum_{i=1}^n v_i \; \text{whereas} \begin{pmatrix} {} v_1 \\ \vdots \\ v_n \end{pmatrix} \text{is just a vertically oriented $n$-tuple.}
3. Consider the situation:
f:X\to Y is a function and e and e' two expressions denoting the same element of X.
We introduce the expression
(e=e')f to
1. Indicate that e and e' denote the same element in X, and 2. return the element of Y which is the value of f under f.
For a simple example,
2+3=5 \Rightarrow (2+3)^2=5^2 =25 = (2+3=5)^2 \, .
4. For an example, which appeared above, combining these notational conversations, consider
\source { \left( \begin{Bmatrix} {} v_1 x_1 \\ \vdots \\ v_n x_n \\ \end{Bmatrix} \xlongequal[\text{basis}]v v \right) } \leftadj F \; ,
which follows from
\source{ v_1x_1 + \dots + v_nx_n \xlongequal[\text{basis}]v v }
and returns the common value
\source{ (v_1x_1 + \dots + v_nx_n)\leftadj F \mathrel{\target =} v\leftadj F } \; .
----------
Here is another approach to the same subject:
\target { \left( \leftadj { \left( M^{\source v}_{\target w} (F) = A =con \begin{pmatrix} {} a_{\green1\blue1} & a_{\green1\blue2} & \dots & a_{\green1\blue n} \\ && \vdots \\ a_{\green m\blue1} & a_{\green m\blue2} & \dots & a_{\green m\blue n} \\ \end{pmatrix} \right) } \source { \begin{pmatrix} {} x_1 \\ \vdots \\ x_n \\ \end{pmatrix} } \right) X_w\inv = \begin{Bmatrix} {} ( w_1 \leftadj a_{1,1} + \dots + w_m \leftadj a_{m,1} & \xlongequal[\text{basis}] w & \source{v_1} \leftadj F ) \source{x_1} \\ & \vdots \\ ( w_1 \leftadj a_{1,n} + \dots + w_m \leftadj a_{m,n} & \xlongequal[\text{basis}] w & {\source{v_n}} \leftadj F ) \source{x_n} \\ \end{Bmatrix} } \leftadj { \xlongequal[\text {linear}]F } \source { \left( \begin{Bmatrix} {} v_1 x_1 \\ \vdots \\ v_n x_n \\ \end{Bmatrix} \xlongequal[\text{basis}]v v \right) } \leftadj F = \source v \leftadj F